Intensifier Used By Female Characters In The Sisterhood Of The Traveling Pants Movie - Lina Yuni Lestari; Ni Luh Sutjiati Beratha; Putu Weddha Savitri (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The title of this study is Intensifier Used by Female Characters In The Sisterhood of the Traveling Pants Movie. It aims to identify and explain one of the women's language features: intensifier. The data was taken from the movie and its movie script. This research applied two theories, the first one proposed by Sardabi and Afghari, which is used to identify the utterances delivered by the characters. Whereas, the second theory is the theory of context of situation by Halliday. This research uses documentation to collect data, documentation obtained through observation, and note-taking technique. Then, classifying the functions of intensifiers used by the female characters based on the theory and analyze the context of the situation. In analyzing data, this research was analyzed qualitatively in a descriptive way. The result shows intensifier